Performance modelling and analysis of Olympic class sailing boats - Reid, A. (University of Newcastle Upon Tyne, 2011)
The work in this thesis is preceded by a Master of Research in Marine Technology project between September 2004 and October 2005. The project was supervised by Professor Martin Downie and was carried out with significant time present in the field, working closely with Olympic sailors from multiple different classes. This project was funded by UK Sport and considered a pilot project to investigate the feasibility of using data logging equipment with GPS in the marine Olympic environment. A series of prototype systems were engineered to meet the requirements specified by the Royal Yachting Association. The engineering and validation of the software and hardware formed a key part of the project to ensure that the results obtained were accurate and repeatable. This included software design within two different software platforms as well as embedded hardware developments. Significant testing and development were implemented in the laboratory as well as on the water during the beginning of the project and as a continuous background task throughout the project. Over eighty days were spent in the field developing and testing hardware and software as well as determining the optimum performance analysis methods. Data loggers were fitted to several Olympic class boats during the evaluation process to ascertain the performance of the data logging system as well as the performance of the boat and crew. Data was logged from the onboard GPS and accelerometers and analysed post training. Later in the project, wind information was also collected and fused together with the onboard data post training. The hypothesis was to demonstrate performance gains in the participating classes through the means of quantitative analysis. Prior to the project the performance analysis had been almost entirely qualitative. Through the course of the project various techniques were developed allowing quantitative performance analysis to supplement the efforts of the training group and coach. Key performance factors were determined by data analysis techniques developed during the project. One of the significant tools developed was a tacking performance analysis routine which analysed multiple different styles of tacks, calculating the distance lost with respect to wind strength and course length resulting in an important strategic tool. Other tools relating to starting performance and straight line speed were also developed in custom software allowing rapid analysis of the data to feed back to the teams in the debrief.